Selected comorbidities of atopic dermatitis: Atopy, neuropsychiatric, and musculoskeletal associations - Silverberg, Jonathan I. (Clin Dermatol, 2017)
Atopic dermatitis (AD) is a chronic pruritic inflammatory skin disease with substantial morbidity and quality of life impairment. There are a number of comorbid health problems that occur in patients with AD, aside from the cutaneous signs and symptoms. Chronic pruritus and inflammation can lead to sleep disturbances and mental health symptoms, which are not mutually exclusive. AD is associated with and may predispose to higher risk of other atopic disorders, including asthma and hay fever. Persons with AD appear to be at higher risk for multiple neuropsychiatric disorders, including depression, attention deficit (hyperactivity) disorder, speech disorders in childhood, headaches, and seizures. There is also a multifactorial association of AD with osteoporosis, injuries, and fractures. Elucidating the comorbidities of AD is important for disease management and improving overall clinical outcomes. This review summarizes recent developments in the atopic and neuropsychiatric comorbidities of AD.